IMPLEMENTATION OF FUZZY LOGIC SYSTEM IN DEVELOPMENT OF THE GREEN CONSTRUCTION ASSESSMENT MODEL IN THE CONSTRUCTION PROCESS FOR BUILDING PROJECTS IN INDONESIA - Triana Putri, Andira
The development of the practice of green constructon in Indonesia is still very poor. This can be caused by a lack of awareness of parties related to construction practices. With the existence of a special system to assess the construction process performance in the management aspects of environmental impacts, it is expected that the practice of green construction can increase. In evaluating something, humans tend to qualitatively assess it first by using linguistic variables before translating it into other input languages such as numerical variables, and in that assessment there must be subjective properties possessed by humans. The purpose of this study is to develop a green construction assessment model for building projects in Indonesia using fuzzy concepts that can overcome the problem of subjective human judgment. The data needed in this study was obtained from practitioners and academics using the questionnaire method. The results obtained from this study are a green construction assessment model with a fuzzy concept consisting of 14 factors and 7 aspects, developed from the assessment preferences of groups of practitioners and academics, and made with the MATLAB program.